Immobilization of saccharomyces cerevisiae on nata de coco effects of agitation rate and nata de coco geometry - Hipolito, Miguel Carlo A.
Many industrial processes utilize biological reactors (bioreactors) for the manufacture of various products, Increasing biocatalyst (cells, enzymes, etc.) concentrations have been shown to be an effective way for improving the performance of bioreactors. To achievethis, immobilization of biocatalysts is done by various mechanisms and using various materials. Nata de coco (NDC), a variant of microbial cellulose derived from coconut milk, is one such material that may be used for immobilization. Saccharomyces cerevisiae was immobilized onto NDC and the effects of agitation rate and NDC geometry during immobilization were determined. A 2-way analysis of variance shows that both factors had a significant effect on the immobilization of yeast. The smaller sized NDC geometries agitated at 50 rpm produced the best results with cell numbers as high as 1.9x10⁸ cells per gram of material. Higher agitation rates (>100rpm) inhibited immobilization due to the reduced contact time between cells and immobilizing material.